Analysis of the Influence of Syariah Bank Financing on Indonesia's Economic Growth in 2019 - 2023 - Rizky, Dimas; Kornitasari, Yenny (Islamic Economics and finance in Focus, 2025)
This research aims to see the influence of Islamic bank financing variables including Sharia Working Capital Financing, Sharia Investment Financing and Sharia Consumptive Financing on Indonesia's economic growth. The research uses a quantitative approach. The type of data used is quantitative data and the data source is secondary data. The ap-proach method used in this research is multiple linear regression analysis. The estimation results show that the Sharia Working Capital Financing variable has a negative effect on Economic Growth, Sharia Investment Financing and Sharia Consumptive Financing have a positive effect on Economic Growth.